Peran Pengasuh (Orangtua) Dalam Mengatasi Keterlambatan Produksi Berbahasa Anak-Anak Penderita Hiperautis - Sainil Amral (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Metro, 2015)
This article is based on the results of the Mini Research on the topic: The Role of Caregivers (parents) in Production Delays Overcoming Speaking Children People Hiperautis (Ethnographic Studies Communication on ‘Valian’ Students Hiperautis sufferers in the city of Jambi). The study focused on the role of parents in children’s language production processes in order to describe hiperautis strategic steps that can be provided as a reference language handling production problems in question. Data obtained with the documentation study diaries by parents who discussed the theories of language acquisition and production. The results showed that, hiperautis child language production is highly dependent on the parental role to motivate and attention to children. Hiperautis child can follow the development and production of language acquisition was belatedly from normal children.